Alterations of the intestinal microbiota in age-related macular degeneration - Zhang, Yuanyuan; Wang, Tianyu; Wan, Zhongqi; Bai, Jianhao; Xue, Yawen; Dai, Rushun; Wang, Minli; Peng, Qing (Frontiers in Microbiology, 2023)
Purpose Age-related macular degeneration (AMD) is the leading cause of vision loss in those over the age of 50. Recently, intestinal microbiota has been reported to be involved in the pathogenesis of ocular diseases. The purpose of this study was to discover more about the involvement of the intestinal microbiota in AMD patients. Methods Fecal samples from 30 patients with AMD (AMD group) and 17 age- and sex-matched healthy controls (control group) without any fundus disease were collected. DNA extraction, PCR amplification, and 16S rRNA gene sequencing of the samples were performed to identify intestinal microbial alterations. Further, we used BugBase for phenotypic prediction and PICRUSt2 for KEGG Orthology (KO) as well as metabolic feature prediction. Results The intestinal microbiota was found to be significantly altered in the AMD group. The AMD group had a significantly lower level of Firmicutes and relatively higher levels of Proteobacteria and Bacteroidota compared to those in the control group. At the genus level, the AMD patient group showed a considerably higher proportion of Escherichia-Shigella and lower proportions of Blautia and Anaerostipes compared with those in the control group. Phenotypic prediction revealed obvious differences in the four phenotypes between the two groups. PICRUSt2 analysis revealed KOs and pathways associated with altered intestinal microbiota. The abundance of the top eight KOs in the AMD group was higher than that in the control group. These KOs were mainly involved in lipopolysaccharide biosynthesis. Conclusion The findings of this study indicated that AMD patients had different gut microbiota compared with healthy controls, and that AMD pathophysiology might be linked to changes in gut-related metabolic pathways. Therefore, intestinal microbiota might serve as non-invasive indicators for AMD clinical diagnosis and possibly also as AMD treatment targets.